2023
DOI: 10.3390/life13081753
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Studies on Genoprotective Effect of Rosa damascena Mill. Hydrosol in Plant and Lymphocyte Test Systems

Abstract: Bulgarian Rosa damascena Mill. is has been known since ancient times for its high-quality oil, hydrosol, and other aromatic products. Rose hydrosol has various biological activities, but no research on its anticytotoxic/antigenotoxic effects exists. This study aimed to assess its defense potential against the genotoxin N-methyl-N′-nitro-N-nitrosoguanidine and to test its cytotoxic/genotoxic activity in plant and human lymphocyte test systems. Endpoints for cytotoxicity (mitotic index and nuclear division index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…The results agree with our previous study, where the application of R. damascena hydrosol in non-toxic concentrations (6% in lymphocyte cultures and 20% in barley) also demonstrated cyto-and genoprotective effects against the alkylating mutagen MNNG [54]. Similar DNA-protective potential was also reported for the R. alba essential oil [2].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results agree with our previous study, where the application of R. damascena hydrosol in non-toxic concentrations (6% in lymphocyte cultures and 20% in barley) also demonstrated cyto-and genoprotective effects against the alkylating mutagen MNNG [54]. Similar DNA-protective potential was also reported for the R. alba essential oil [2].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies demonstrated that treatment with R. alba L. and R. damascena Mill. hydrosols (3-20%) also increased the frequency of chromosome injuries and micronuclei to a low extent in the used test systems [53,54]. The observed effect is probably due to the chemical compounds in the hydrosols that can interact with both H. vulgare and human lymphocyte DNA.…”
Section: Discussionmentioning
confidence: 87%